Mechanism studies of hydrothermal cold sintering of zinc oxide at near room temperature. Issue 8 (8th February 2019) - Kang, Xiaoyu; Floyd, Richard; Lowum, Sarah; Cabral, Matthew; Dickey, Elizabeth; Maria, Jon‐Paul
Abstract: Zinc oxide densification mechanisms occurring during the cold sintering process (CSP) are examined by investigating specifically the effects of ion concentration in solution, temperature, pressure, and die sealing. The experiments suggest that mass transport through solution is a primary densification mechanism and that either a pre‐loaded solution or grain dissolution can supply migrating ions. Additionally, results indicate cold sintering zinc oxide requires a critical pressure value, above which densification is relatively pressure independent under the majority of process conditions. This critical pressure is related to thermal expansion of the liquid and determines the uniaxial pressure threshold for densification. The data supports a three‐stage interpretation of cold sintering, which includes quick compaction, grain rearrangement, and dissolution‐reprecipitation events. Further, it is observed that under the lowest temperature conditions a net decrease in particle size can occur during the cold sintering process.